A study of certain ecological aspects pertaining to a Leucadendron laureolum community at the Silver Mine Nature Reserve, South Africa - Kathan, Louis (Department of Biological Sciences, 2016)
This survey was conducted in three phases, viz. 1. The Braun-Blanquet phytosociological technique was used to describe the vegetation of the study area and adjacent areas. Two major communities, based on plant community structure environmental factors and floristics, are recognised. 2. A determination of phytomass was obtained from five sites in the study area by means of clip-plots from a plant community of post-fire ages of about twenty years, ten years and one year. In this study three structural elements of the fynbos were distinguished viz. proteoid, restioid and "remainder". It was established that the average growth rate for the approximately 20 year old proteoid community was 656 kg/ha/yr and for the ten year old community it was 309,2 kg/ha/yr. The marked difference in growth rate of the proteoid element is due to a slow growth rate until the community is some ten years old and thereafter there is a rapid increase in growth. The restioid component tended to show a decrease in phytomass with increasing age viz. 225, 123,4 and 207,3 kg/ha for one year, ten and approximately twenty year post-fire ages. For th e "remainder" it was found that this also decreased with increasing age viz. 380, 54,5 and 25,5 kg/ha for one year, ten and approximately twenty year post fire ages. 3. The effect of the June fire on the bush-cut vegetation of the study area in the Silver Mine Nature Reserve is discussed. The regeneration of plant species was monitored for twelve months in five randomly selected, permanently marked plots. Field observation revealed that 65,1% of the species regenerated from underground organs, such as rhizomes and corms, and the remaining 34,9% of the plant species regenerated from seed. Based on the phytomass study and rate of regeneration of the plant species in the area it appears that an approximate 15 year fire interval is the most acceptable. Bibliography: pages 104-119.